Anguish and accolades: a psychological therapy for music performance anxiety : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, New Zealand - Tarrant, Ruth Annette Cobham (Massey University, 2003)
Music performance anxiety (MPA) is widespread among professional, amateur, and student-musicians and -singers. While a certain level of anxiety is necessary for optimal performance, in some instances anxiety can reach levels where the performance is impaired and the performer's enjoyment reduced. Despite the negative effects of MPA, there has been relatively little research in the area, and studies to date have focussed almost exclusively on classical musicians, with little known about jazz musicians. Particular problems within the MPA research include the absence of a clear definition of MPA, the absence of an established measurement tool, and an incomplete set of agreed influences on MPA. Various studies typically limit their investigation to only one or a few possible influential factors. Treatment studies have investigated a range of approaches based on varying understandings of factors that define and influence MPA. Assessment of treatment outcomes has also varied, due to a lack of equivalence among measurement tools. The present research comprises two studies. Study One, an exploratory survey of a group of Conservatorium musicians, aimed to gain an understanding of MPA as a construct, to investigate the prevalence of MPA, to develop an appropriate measure for MPA, and to clarify a set of factors that can influence MPA. Comparisons were made for gender and music genre. Participants comprised 39 musicians from the Conservatorium of Music at Massey University. Study One differed from most previous studies, by investigating a broad range of factors associated with MPA. Results of Study One indicate that MPA can be defined as a four-part construct comprising physiological, cognitive, affective, and behavioural components. While the four components interact, they can also operate independently, feeding back into the arousal. Factors influencing MPA can be categorised into three broad groups: personality factors, experience (including preparation and performing history), and situational variables. Factors from these three broad groups of influences appear to be present in different combinations and intensities for individual performers, varying at different stages of their careers, and variously influencing MPA, depending also on the type of performing situation. A defining feature of participants in Study One was that the widespread, marked level of MPA experienced prior to performing, was generally maintained into the performance itself. While females tended to report more MPA than males, and classical participants reported more than jazz participants, there were few significant differences between gender, and music genre. The findings of Study One informed the development of Study Two. Study Two aimed to develop, trial, and evaluate a psychological intervention for MPA in a group of conservatorium musicians. This study used a quasi-experimental approach to investigate the efficacy of the intervention. The intervention was conducted over six 1-11/4 hour sessions. Twenty-five participants began the intervention, and 14 completed. Participants who did not complete the intervention, but who provided pre-test data only, provided a comparison group for participants who completed the intervention. On the basis that different individuals will experience MPA according to their own particular combination of influential factors, the intervention targeted the four components of MPA and the three broad groups of influential factors of MPA, identified in Study One. The intervention included a particular focus on the role of preparation and the role of attention during performance. M-PAS scores reduced significantly between pretest and follow-up. Results suggest the intervention had a positive effect on the functioning of most participants, assisting them to modify or manage some aspects of MPA that had personal relevance for them. The present study has contributed to the understanding of MPA and its treatment. The particular therapeutic approach of the present study appeared to benefit most completers. The group therapy situation may not have been appropriate for some participants, particularly those who may have perceived the group context as another demanding performance situation. Suggestions for future research include the need for an appropriate diagnostic instrument for MPA, and clarification of the results of the present study with a larger sample. Finally, there is a need to extend the investigation of music performance anxiety by referring to the literature in other performance domains, particularly the domain of sports performance, which is relevant to music and which has a rapidly developing performance literature.
Keywords: Performance psychology; Jazz musicians; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology